2021
DOI: 10.1111/exd.14395
|View full text |Cite
|
Sign up to set email alerts
|

Topical cannabis‐based medicines – A novel adjuvant treatment for venous leg ulcers: An open‐label trial

Abstract: Venous leg ulcers are highly prevalent lower limb integumentary wounds that remain challenging to heal despite the use of evidence-based compression therapies. A multitude of adjuvant treatments has been studied but none have demonstrated enough efficacy to gain adoption into treatment guidelines. Global attention on Cannabis-Based Therapies is increasing and has been driven by quantum scientific advancements in the understanding of the endocannabinoid signalling system. Topical Cannabis-Based Medicines repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 73 publications
(174 reference statements)
0
18
0
Order By: Relevance
“…The results showed rapid wound closure of the previously nonhealing venous leg ulcers. This evidence suggests that TCBM may be an effective adjuvant in conjunction with compression therapy 23 . No randomized controlled trials have been carried out though, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed rapid wound closure of the previously nonhealing venous leg ulcers. This evidence suggests that TCBM may be an effective adjuvant in conjunction with compression therapy 23 . No randomized controlled trials have been carried out though, and further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an extensive literature search, the authors did not find any research investigating the use of CBD in SSc-DU treatment. Only seven published reports have investigated CBD treatment of skin ulcers (Table 3 ): 6 , 18 23 a single case report, 6 two case series, 19 , 20 and one prospective open-label trial with different reports from the same study. 18 , 21 23 Generally, the studies reported small patient series (between 3 and 33 patients) with varied dosages and modalities of CBD administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a CBD-containing hydrogel dressing based on the ion-crosslinked interaction between Zn 2+ ions and the alginate polymer was recently reported to accelerate wound healing in vivo [ 125 ]. Based on the promising preclinical results, corresponding cannabinoid effects have meanwhile been investigated in patients with venous leg ulcers [ 126 ]. Here, liposomal formulations with a mixture of CBD, THC and other substances proved to be beneficial.…”
Section: The Endocannabinoid System In the Skinmentioning
confidence: 99%
“…Finally, data from a recent small open-label trial suggest that cannabinoids are a therapeutic option for rapid wound closure of previously non-healing venous leg ulcers [ 126 ]. This study tested the wound healing properties of cannabinoids in 14 patients with ulcers due to chronic venous hypertension and existing venous insufficiency.…”
Section: Clinical Trials With Cannabinoidsmentioning
confidence: 99%